Mechanism For The Development Of The Education Market In The Context Of Economic Transformation - Abdufattoevna, Hamidova Aziza (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article describes characteristics of price and demand for educational services in the market of educational services, interdependence of education and production, structural changes in the system of higher education, characteristics of individual demand for educational services, internal and external factors, level of demand for educational services. The factors of individual competitiveness as an element were studied.